A new approach of scale invariance for complex system and application in power line communication modelling - Minh, Le Thi Tinh; Retiere, Nicolas; Quang, Nguyen Dinh (Vietnam Journal of Science and Technology, 2017)
In the context of the incessant development of sustainable energy and ICT (Information and Communications technology) in power systems, power system becomes more and more intelligent, efficient and economic. However, using electrical infrastructure carrying information communication causes complexities in modeling and simulating. To overcome the problem of modeling, a new approach based on scale invariance theory, scale invariance, is presented in many papers and in various fields. Scale invariance method shows a strong link between a network topology and its performances through a coefficient exponent. In this paper we propose to use this method for modeling power line communication by considering only the input impedance of system. This approach will be tested for not only a general case study but also for an opened circuit without attenuation and bruit. The result is compared with the classical method.